COMPARATIVE STUDY OF LIVER HISTOPATHOLOGY AND TRANSAMINASE LEVELS IN DIABETIC WISTAR RATS INDUCED BY ALLOXAN AND STREPTOZOTOCIN - Hidayah, Ainun Nafisa Riski; Purnawati, Ratna Damma; Pralampita, Pulong Wijang; Ismail, Akhmad (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2026)
Background: Diabetes mellitus (DM) is a metabolic disorder characterized by elevated blood glucose levels. Experimental models using male Wistar rats (Rattus norvegicus) induced with alloxan (ALX) or streptozotocin (STZ) are widely applied to explore therapeutic strategies. However, several studies have reported that ALX has greater limitations compared with STZ. Objective: To analyze the differential effects of ALX and STZ as diabetogenic inducers in Wistar rats based on liver histopathology, serum glutamic oxaloacetic transaminase (SGOT), and serum glutamic pyruvic transaminase (SGPT) levels. Methods: A post-test only control group design with simple randomization was employed. Forty-two male Wistar rats weighing ≥200 g were assigned into seven treatment groups. Independent variables included ALX and STZ at graded doses, while dependent variables were liver histopathology, SGOT, and SGPT. Histopathology was assessed using the Manja Roenigk scoring system, and enzyme levels were measured by enzymatic methods. Results: Significant differences were observed between ALX and STZ in liver histopathology (p<0.001) and SGPT levels (p=0.001), but not in SGOT (p=0.199). Histopathological findings between ALX- and STZ-induced groups were relatively comparable at equivalent doses. In contrast, SGOT and SGPT results indicated that ALX may induce resistance. Conclusion: ALX and STZ caused comparable hepatic damage, but STZ exhibited more stable blood biomarker profiles.